Presence of Mycobacterium leprae genotype 4 in environmental waters in Northeast Brazil - Holanda, Maísa Viana de (2017)
INTRODUCTION: This study quantified Mycobacterium leprae bacilli in environmental water samples from five municipalities in the State of Ceará by quantitative polymerase chain reaction (qPCR) and compared the identified genotypes with those obtained from leprosy patient biopsies. METHODS: We collected five replicas from each of the 30 selected reservoirs and skin lesion biopsies from 25 new leprosy cases treated at a reference center in Fortaleza, Ceará from 2010 to 2013. The 16S rRNA gene region of M. leprae was amplified by qPCR and a standard curve was created with the pIDTBlue 16SrRNAMlep plasmid. The Juazeiro do Norte water samples and the biopsies were genotyped (single nucleotide polymorphism [SNP] 1 to 4) and the SNP 4 genotypes were subtyped. RESULTS: Of the 149 water samples analyzed, 54.4% were positive for the M. leprae DNA. The M. leprae bacilli copy number ranged from 1.42 × 10 -1 to 1.44 × 10 + 2 . Most biopsies showed SNP type 4 (64%), while all samples from Juazeiro do Norte were SNP type 4, with subtype 4-N appearing at the highest frequency. CONCLUSIONS: We suggest that environmental waters containing M. leprae bacilli play an important role in disease transmission, justifying PGL-1 seropositivity in individuals living in areas where there is no reported case, and in leprosy cases individuals who report no previous contact with other case. Therefore, further investigation is needed to clarify disease transmission in this region and to explore the role of the environment. We also suggest that in this area surveillance for leprosy cases should be intensified.